To Evaluate the Knowledge, Attitude and Practice of Hand Washing and to Determine the Factors Involved in Poor Hand Washing Among the Primary School Students of Bannu (Medical Forum Monthly, 2021)
Objective: To evaluate the knowledge, attitude and practice of hand washing and to determine the factors involved in poor hand washing among the primary school students of Bannu.Study Design: Descriptive Cross-Sectional StudyPlace and Duration of Study: This study was conducted at the in various primary school students of Bannu, KPK, Pakistan from December, 2019 to March, 2020 for a period of 04 months.Materials and Methods: A sample of 200 subjects was selected by consecutive sampling technique. Total 4 schools were selected. Two schools from public sector and two from private sector were selected through convenience sampling. Study tool was a questionnaire. Data was analyzed by descriptive analysis plan.Results: Out of 200 students 169 were males and 31 were females. 55 % of the students wash their hands before eating and 60.5% of the students wash their hands after using toilet. 47.5% of the students use soap for handwashing while 52.5 % of the students reported that they do not use soap. Frequency of handwashing practice was less in those students whose parents were not formally educated. Also, percentage of handwashing was more in those students whose maternal education was high. Almost all of the students did not know about the WHO method of hand washing. Majority of the students (85%) reported that they dry their hands with towel.Conclusion: Education is an important factor regarding handwashing behavior. Interventions regarding handwashing should be carried out to improve handwashing behavior. Maternal education in this case will be very important. Also, most of the schools are lacking facilities of hand washing, so facilities for handwashing should be provided.